Exercise as medicine evidence-based findings on : how exercise heals various diseases, how effective are yoga, meditation, tai chi & qigong and how to exercise for different illnesses. (Consumers Association of Penang, 2007)
This book provides the A-Z of what medical science knows about exercise, health and disease. It also shows you how to exercise for the various illneddes.